Теплотехника учебное пособие - Крайнов, А. В. специалист в области теплотехники доцент Томского политехнического университета, кандидат физико-математических наук 1974- (Изд-во ТПУ, 2012)
The study aid covers the basic theoretical data, the description of modern laboratory installations, formulated tasks and questions for class and self - study for students and the set of test materials to assess their knowledge. In developing of the educational material the combination of domestic and foreign technologies of the teaching the discipline in the higher technical school is presented. The study aid is intended for the students of technical specialities studying thermal engineering in English. The study aid has been compiled according to modern requirements to the future engineer. The complexity of the presentation allows using the study aid in the frame of the common international educational programs, in the sphere of the elite technical education and in advanced training or for self-study.